The Urgency of Marriage Disability from the Perspective of Fiqh and Compilation of Islamic Law (Khi) - Evanurfitriani, Evanurfitriani (Riwayat: Educational Journal of History and Humanities, 2025)
Marriage is an inner bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the One Godhead". Marriage will play a role after each mass of people is ready to play a positive role in realizing the purpose of marriage itself. The same thing is in line with Law No. 1 of 1974 concerning marriage article 1, which reads: However, the marriage has not fulfilled the formal law of marriage because it has not been recorded with the authorized registrar/does not have a marriage certificate book. Therefore, even though the marriage is materially valid, but formally the marriage is not yet valid, so that it is forever considered that there has never been an exception marriage if it can be proven by the Marriage Certificate issued by the Marriage Registrar. That by recording the marriage in the Office of Religious Affairs, the marriage has received legal certainty and protection, including against the consequences arising from the said marriage, a woman who marries a man and her marriage is not recorded in the marriage registrar, if the husband is negligent or neglects his obligations, if a wife demands from her husband to fulfill his obligations in court as stipulated in the article 34 paragraph (3) of Law No. 1 of 1974 concerning marriage or will sue her husband in court for having committed intercession as stipulated in article 9 of Law No. 23 of 2004 concerning the elimination of domestic violence (KDRT), then she will experience difficulties due to the absence of authentic evidence of the existence of a legal relationship in the form of marriage between the wife and her husband